Distributed temperature sensing system based on a densely spaced FBG array for small fire recognition. (July 2021) - Wang, Jiaqi; Li, Zhengying; Fu, Xuelei; Wang, Honghai; Jiang, Desheng
Abstract: A distributed temperature sensing (DTS) system based on a densely spaced fiber Bragg grating (FBG) array is proposed in this work for small fire recognition. A large capacity identical FBG array with centimeter-scale grating spacing is employed to build a high-density sensor network, increasing the probability that the small fire will affect at least one FBG. To retrieve the sensing information, we exploit an FBG interrogation system based on optical time-domain reflectometry and swept laser techniques, together with a fiber section (FS) spectrum interrogation method. The sensing technique consists in scanning the sensing array by means of a low-coherence wavelength-tunable pulsed laser and in reconstructing and analyzing the returned spectra signals. The sensing performance of the proposed DTS system is studied by theoretical analysis and experimental demonstration, verifying the feasibility and superiority of the densely-spaced FBG array based DTS system for small fire recognition and location. Highlights: The gratings act like the enhanced Raman scattering elements in the fiber. The effect of the system parameters on the sensing performance is analyzed. Build a low-noise wavelength-tunable ring laser with a coherence length of 19 mm. A small target shorter than the spatial resolution is detected with high accuracy. The method is preferred for small fire recognition in fire prevention applications.